THE UTILIZATION OF INTERACTIVE POWERPOINT MEDIA ON STUDENTS' LEARNING INTEREST IN CULTURAL DIVERSITY MATERIALS IN ELEMENTARY SCHOOL - Farahdhiva Qotrunnada Fajrin; Vincentia Della Prawesti; Risma Savitri; Cholifah Tur Rosidah; Susi Hermin Rusminati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The success of a learning is influenced by students' learning interest. at the elementary school level there are several subjects that students must follow, one of which is social studies. however, based on the results of previous journal studies, it was stated that there were problems found, namely the low interest in student learning because learning was monotonous. in this study the solution given to this problem is by using interactive powerpoint media. The method used in this research is literature study. Based on the results of research on literature studies, the use of interactive powerpoint as a social study learning media in elementary schools can foster motivation and improve student learning outcomes.